Pendampingan Siswa dalam Mengatasi Kesulitan Matematika Pada Pelajaran Transformasi Geometri Materi Rotasi di MTs Negeri Gowa - Nurfadila, Suci; Rasdiana; Guntur, Anantasia; Suharti; Rezki Yulianti, Sri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Learning mathematics on geometric transformations, particularly rotations, remains a challenge for most students at Gowa State Islamic Junior High School (MTs Negeri Gowa). Most students still face numerous difficulties in learning mathematical concepts related to geometric transformations, particularly rotations. These difficulties include a weak understanding of the concept, difficulty in determining the center of rotation and angle sizes, and inadequate ability to visualize geometric shapes. This study aims to explore the effectiveness of student tutoring in helping students overcome difficulties in learning rotation mathematics. This study used a qualitative approach, focusing on ninth-grade students at Gowa State Islamic Junior High School. Data collection methods included observation, interviews, and learning achievement tests. The tutoring methods included intensive teaching, the use of visual media, and providing increasingly challenging exercises tailored to the students' ability levels. The results of the activity show that student mentoring is able to improve understanding of the concept of rotation, reduce errors in solving problems, and increase student confidence in learning mathematics.. Thus, student tutoring is an effective strategy for overcoming difficulties in learning mathematics on geometric transformations, particularly rotations.